Literature Review: Analisis Kandungan Macronutrients Dan Micronutrients Pada Pizza Dan Salad Sayur - Agnaneja Kaleena Setiawan; Annisa Surya Salsabila; Shifa Anggraeni Arofah; Wal Muzhoffar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Junk food is processed food that is quickly processed and has an affordable price, but has low nutritional content. This study aims to compare the nutritional content between junk food and healthy food, especially in pizza and salad, and explain the impact of these two foods on health. Based on the results of the literature review, junk food such as pizza has a high content of calories, fat, and sodium which when consumed excessively can cause adverse effects such as the risk of obesity, heart disease, and hypertension. In contrast, salads are rich in fiber, low in calories, and high in minerals such as calcium and magnesium, which are beneficial and healthy for the body. The results of the study are expected to provide understanding to the public about the importance of choosing healthy foods to reduce the risk of degenerative diseases.